Café au Lait macules or Cause for Concern? Unravelling it’s Secret with Histology and Dermoscopic Findings - Purvesh Fale; Rahangdale, Vishwas; Aniket Ratnaparkhi; Mahesh M. Unni (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Café au lait macules (CALMs) are common, benign, light-brown skin patches that usually appear in childhood. Typically under 2 cm in size and found on sun-protected skin, they are present in about 2–3% of newborns and a third of school-aged children. While single CALMs are harmless, multiple lesions may signal underlying disorders like neurofibromatosis type I (NF1) or McCune-Albright syndrome (MAS). A case study of a 3-year-old boy with enlarging CALMs highlights the need for clinical, dermoscopic, and histological assessments to rule out associated syndromes such as NF1, MAS, segmental neurofibromatosis, and Watson syndrome, though the child showed no signs of these. CALMs carry no risk of malignancy, but cosmetic concerns often lead to treatment. High-fluence Q-switched 1,064-nm Nd:YAG laser therapy has proven safe and effective, achieving over 75% clearance in about half of patients with minimal side effects, making it a valuable option for managing these lesions.